PVTF flexible piezoelectric film with double-layer structure and preparation method and application of PVTF flexible piezoelectric film
By introducing non-solvent phase water into the PVDF-TrFE flexible piezoelectric film to form a film with a double-layer structure, the problems of output performance and voltage tolerance under high voltage polarization are solved, and efficient piezoelectric output and high voltage tolerance are achieved, which are suitable for flexible piezoelectric sensors.
Patent Information
- Application Number
- CN202411856880.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-17
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2044-12-17
AI Technical Summary
The existing PVDF-TrFE flexible piezoelectric films cannot take into account high output performance and high voltage tolerance under high voltage polarization, making it difficult to achieve excellent performance in sensor applications.
Using the preparation method of a two-layer structure, by introducing non-solvent phase water into the PVDF-TrFE film, the pore layer thickness is controlled to recombinate with the dense layer, and a composite structure with porous and dense layer is formed by casting method and polarization treatment.
It realizes the maintenance of high-voltage electrical output performance under high voltage conditions, while improving the flexibility and strength of the film, and is suitable for the application of flexible piezoelectric sensors.
Smart Images

Figure CN119768027A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of piezoelectric materials, and in particular to a PVTF flexible piezoelectric film with a double-layer structure and a preparation method and application thereof. Background Art
[0002] Flexible piezoelectric sensors are a new type of energy sensor that converts mechanical energy into electrical energy, providing a clean and renewable energy source. They are widely used in energy harvesters, health detection and wearable devices due to their self-powered, high sensitivity, light weight and high softness.
[0003] Polyvinylidene fluoride trifluoroethylene (PVDF-TrFE) is a semi-crystalline polymer with flexibility and excellent piezoelectric properties. Researchers usually use electrospinning, mechanical stretching, adding nucleating agents or fillers to make PVTF have a high content of electroactive β phase, but the microstructure of the film also has a great influence on the piezoelectric output. Therefore, microstructural design of PVTF has become another hot spot in piezoelectric research.
[0004] The porous structure can make the film compressible. Compared with the dense film, it will produce greater strain under the same stress conditions, which is conducive to the directional arrangement of the -CH2- / -CF2- dipoles of PVDF-TrFE under stress, which will increase the induced charge accumulation area and total polarization, thereby increasing the output. However, the porous film cannot withstand high-voltage polarization compared with the dense film. Therefore, how to combine the pore structure and the dense structure in a film so that it can withstand relatively high voltage and have good performance output is of great significance to promote the research of flexible piezoelectric sensors. Summary of the invention
[0005] The purpose of the present invention is to provide a PVTF flexible piezoelectric film with a double-layer structure and a preparation method and application thereof, and to compound a pore structure with a dense structure to obtain good piezoelectric output.
[0006] In order to achieve the above object, the first aspect of the present invention provides a method for preparing a PVTF flexible piezoelectric film having a double-layer structure, comprising the following steps:
[0007] The non-solvent phase, the solvent phase and the PVTF are mixed to obtain a uniform solution; wherein the non-solvent phase and the solvent are mutually soluble, and the PVTF is soluble in the solvent phase but insoluble in the non-solvent phase;
[0008] The obtained uniform solution is evenly spread on a glass plate by a casting method, and then placed in a vacuum oven for evaporation at room temperature to obtain an initial film;
[0009] The initial film is annealed, cooled, and polarized to obtain a piezoelectric film.
[0010] Preferably, in the above method for preparing a PVTF flexible piezoelectric film with a double-layer structure, the non-solvent phase is water and ethanol; the solvent phase is tetrahydrofuran and acetone, and PVTF is PVDF-TrFE composed of PVDF and TrFE in a molar ratio of 1-4. More preferably, PVTF is PVDF-TrFE(70 / 30).
[0011] Preferably, in the above method for preparing a PVTF flexible piezoelectric film with a double-layer structure, the feeding mass ratio of tetrahydrofuran to PVTF is 7-10, and the feeding mass ratio of water to PVTF is x, where 0 < x ≤ 0.9. More preferably, the feeding mass ratio of PVTF to THF is 1:9.
[0012] Preferably, in the above method for preparing a PVTF flexible piezoelectric film with a double-layer structure, the non-solvent phase, the solvent phase and PVTF are mixed evenly by stirring to obtain a homogeneous solution, where the stirring speed is 500-1000 rpm and the stirring time is 1-5 h. More preferably, the stirring speed is 800 rpm and the stirring time is 3 h.
[0013] Preferably, in the above method for preparing a PVTF flexible piezoelectric film with a double-layer structure, the annealing temperature is 100-150 °C and the annealing time is 2-6 h. More preferably, the annealing temperature is 140 °C and the annealing time is 5 h.
[0014] Preferably, in the above method for preparing a PVTF flexible piezoelectric film with a double-layer structure, the polarization is specifically as follows:
[0015] The cooled film is cut into squares and aluminum electrodes are attached to obtain an initial device; the obtained initial device is subjected to oil bath polarization. More preferably, the film is cut into 13 mm * 13 mm squares and 10 mm * 10 mm aluminum electrodes are attached.
[0016] Preferably, in the above method for preparing a PVTF flexible piezoelectric film with a double-layer structure, the oil bath polarization temperature is 60 °C, the polarization voltage is 2500 V-5800 V, and the polarization time is 20-60 min. More preferably, the polarization time is 30 min.
[0017] Preferably, in the above method for preparing a PVTF flexible piezoelectric film with a double-layer structure, after polarization, it further includes encapsulation, specifically:
[0018] Copper tapes are connected to the upper and lower surfaces of the polarized film and encapsulated with polyimide tape to obtain a flexible piezoelectric device.
[0019] The second aspect of the present invention is to provide a PVTF flexible piezoelectric film with a double-layer structure. The flexible piezoelectric film is prepared by the preparation method of the flexible piezoelectric film, and has a double-layer composite structure of a dense layer and a porous layer. The porous layer and the dense layer are combined, and the compressibility of the porous layer is used to improve the piezoelectric output while maintaining the flexibility and strength of the PVTF piezoelectric film.
[0020] The third aspect of the present invention is to provide an application of a PVTF flexible piezoelectric film having a double-layer structure in a flexible piezoelectric sensor.
[0021] The beneficial effects of the present invention are:
[0022] The present invention proposes a PVTF flexible piezoelectric film with a double-layer structure and a preparation method thereof, which realizes the composite of different pore layer thicknesses and a dense layer by introducing non-solvent phase water and controlling the added amount, while maintaining the flexibility and strength of the film.
[0023] The present invention proposes a PVTF flexible piezoelectric film with a double-layer structure and a preparation method thereof. The prepared PVTF flexible piezoelectric film with a double-layer structure has a layer of pore structure, which will produce greater strain under stress conditions, which is beneficial to the directional arrangement of the -CH2- / -CF2- dipoles of PVDF-TrFE under stress, increasing the induced charge accumulation area and the total polarization, thereby improving the piezoelectric output.
[0024] The piezoelectric film preparation process of the present invention is simple, the preparation cycle is short, and the raw materials are easily available, so the preparation cost is low, which is conducive to mastering and promoting. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 It is a scanning electron microscope image of the cross section of the thin film containing a double-layer structure prepared in Examples 1-1, 2-1, 3-1, and 4-1 of the present invention.
[0026] Figure 2 This is a graph of the open circuit voltage of the film having a double-layer structure after polarization prepared in Example 3-1 of the present invention.
[0027] Figure 3 This is an open circuit voltage diagram of the film having a double-layer structure prepared in Example 3-2 of the present invention after polarization. DETAILED DESCRIPTION
[0028] The specific embodiments of the present invention are described in detail below, but it should be understood that the protection scope of the present invention is not limited by the specific embodiments.
[0029] Example 1-1
[0030] Preparation of a PVTF flexible piezoelectric film:
[0031] 2g THF and 0.2222g PVDF-TrFE (70 / 30) were added to a glass sample bottle in sequence, and stirred on a magnetic stirrer at 800rpm for 3h to obtain a uniform solution. The solution was evenly spread on a glass plate by casting, and evaporated and volatilized in a vacuum oven at room temperature to obtain an initial film. The initial film was placed in a blower and annealed at 140℃ for 5h, then cooled in the oven, and then the film was cut into 13mm*13mm squares and affixed with 10mm*10mm aluminum electrodes to obtain the initial device. The initial device was oil-bath polarized at 60℃ and a polarization voltage of 5800V for 30min, then the film was wiped clean, copper tape was connected to its upper and lower surfaces, and it was encapsulated with polyimide tape to obtain a flexible piezoelectric device.
[0032] Example 1-2
[0033] This embodiment is the same as embodiment 1-1, except that the polarization voltage is 2500V.
[0034] Example 2-1
[0035] Preparation of a PVTF flexible piezoelectric film with a double-layer structure:
[0036] 0.06g deionized water, 1.8g THF, and 0.2g PVDF-TrFE (70 / 30) were added to a glass sample bottle in sequence, and stirred on a magnetic stirrer at 800rpm for 3h to obtain a uniform solution. The solution was evenly spread on a glass plate by casting, and evaporated and volatilized in a vacuum oven at room temperature to obtain an initial film. The initial film was placed in a blower and annealed at 140℃ for 5h, then cooled in the oven, and the piezoelectric film was cut into 13mm*13mm squares, and 10mm*10mm aluminum electrodes were attached to obtain the initial device. The initial device was oil-bath polarized at 60℃ and a polarization voltage of 4900V for 30min, then the film was wiped clean, copper tape was connected to its upper and lower surfaces, and it was encapsulated with polyimide tape to obtain a flexible piezoelectric device.
[0037] Example 2-2
[0038] This embodiment is the same as embodiment 2-1, except that the polarization voltage is 2500V.
[0039] Example 3-1
[0040] Preparation of a PVTF flexible piezoelectric film with a double-layer structure:
[0041] 0.12g deionized water, 1.8g THF, and 0.2g PVDF-TrFE (70 / 30) were added to a glass sample bottle in sequence, and stirred on a magnetic stirrer at 800rpm for 3h to obtain a uniform solution. The solution was evenly spread on a glass plate by casting, and evaporated and volatilized in a vacuum oven at room temperature to obtain an initial film. The initial film was placed in a blower and annealed at 140℃ for 5h, then cooled with the oven, and the piezoelectric film was cut into 13mm*13mm squares, and 10mm*10mm aluminum electrodes were attached to obtain the initial device. The initial device was oil-bath polarized at 60℃ and a polarization voltage of 4000V for 30min, then the film was wiped clean, copper tape was connected to its upper and lower surfaces, and it was encapsulated with polyimide tape to obtain a flexible piezoelectric device.
[0042] Example 3-2
[0043] This embodiment is the same as embodiment 3-1, except that the polarization voltage is 2500V.
[0044] Example 4
[0045] Preparation of a PVTF flexible piezoelectric film with a double-layer structure:
[0046] 0.15g deionized water, 1.5g THF, and 0.1667g PVDF-TrFE (70 / 30) were added to a glass sample bottle in sequence, and stirred on a magnetic stirrer at 800rpm for 3h to obtain a uniform solution. The solution was evenly spread on a glass plate by casting, and evaporated and volatilized in a vacuum oven at room temperature to obtain an initial film. The initial film was placed in a blower and annealed at 140℃ for 5h, then cooled in the oven, and the piezoelectric film was cut into 13mm*13mm squares, and 10mm*10mm aluminum electrodes were attached to obtain the initial device. The initial device was oil-bath polarized at 60℃ and a polarization voltage of 2500V for 30min, then the film was wiped clean, copper tape was connected to its upper and lower surfaces, and it was encapsulated with polyimide tape to obtain a flexible piezoelectric device.
[0047] The relative β-phase content and crystallinity of the flexible piezoelectric film obtained in the embodiment were tested by Fourier transform infrared spectrometer and differential scanning calorimeter. The absolute β-phase content is the product of the relative β-phase content and the crystallinity. The output performance of the flexible piezoelectric device obtained in the embodiment was tested by electrometer and multimeter.
[0048] Example 5
[0049] Preparation of a PVTF flexible piezoelectric film with a double-layer structure:
[0050] 0.15g ethanol, 1.17g acetone, and 0.1667g PVTF (PVDF-TrFE with a molar ratio of 1) were added to a glass sample bottle in sequence, and stirred on a magnetic stirrer at 1000rpm for 1h to obtain a uniform solution. The solution was evenly spread on a glass plate by casting, and evaporated and volatilized in a vacuum oven at room temperature to obtain an initial film. The initial film was placed in a blower and annealed at 100℃ for 6h, then cooled with the oven, and the piezoelectric film was cut into 13mm*13mm squares, and 10mm*10mm aluminum electrodes were attached to obtain the initial device. The initial device was oil-bath polarized at 60℃ and a polarization voltage of 2600V for 30min, then the film was wiped clean, copper tape was connected to its upper and lower surfaces, and it was encapsulated with polyimide tape to obtain a flexible piezoelectric device.
[0051] Example 6
[0052] Preparation of a PVTF flexible piezoelectric film with a double-layer structure:
[0053] 0.15g water, 1.7g acetone, and 0.1667g PVTF (PVDF-TrFE with a molar ratio of 2) were added to a glass sample bottle in sequence, and stirred on a magnetic stirrer at 900rpm for 3h to obtain a uniform solution. The solution was evenly spread on a glass plate by casting, and evaporated and volatilized in a vacuum oven at room temperature to obtain an initial film. The initial film was placed in a blower and annealed at 150℃ for 2h, then cooled with the oven, and the piezoelectric film was cut into 13mm*13mm squares, and 10mm*10mm aluminum electrodes were attached to obtain the initial device. The initial device was oil-bath polarized at 60℃ and a polarization voltage of 2500V for 20min, then the film was wiped clean, copper tape was connected to its upper and lower surfaces, and it was encapsulated with polyimide tape to obtain a flexible piezoelectric device.
[0054] Example 7
[0055] Preparation of a PVTF flexible piezoelectric film with a double-layer structure:
[0056] 0.15g water, 1.6g acetone, and 0.1667g PVTF (PVDF-TrFE with a molar ratio of 4) were added to a glass sample bottle in sequence, and stirred on a magnetic stirrer at 500rpm for 5h to obtain a uniform solution. The solution was evenly spread on a glass plate by casting, and evaporated and volatilized in a vacuum oven at room temperature to obtain an initial film. The initial film was placed in a blower and annealed at 120℃ for 3h, then cooled with the oven, and the piezoelectric film was cut into 13mm*13mm squares, and 10mm*10mm aluminum electrodes were attached to obtain the initial device. The initial device was oil-bath polarized at 60℃ and a polarization voltage of 2500V for 60min, then the film was wiped clean, copper tape was connected to its upper and lower surfaces, and it was encapsulated with polyimide tape to obtain a flexible piezoelectric device.
[0057] The properties of the PVTF flexible piezoelectric films prepared in Examples 1 to 4 are as follows:
[0058] Table 1: Performance of PVTF flexible piezoelectric film with double-layer structure
[0059]
[0060]
[0061] Table 2: Output performance of PVTF flexible piezoelectric film with double-layer structure
[0062]
[0063] Figure 1 The scanning electron microscope images of the cross-section of the film containing the double-layer structure prepared in Examples 1-1, 2-1, 3-1 and 4. It can be seen that as the amount of non-solvent phase water added increases, the porous layer becomes thicker and the dense layer becomes thinner, indicating that the film structure prepared in the present invention can be artificially controlled.
[0064] Figure 2 , Figure 3 It is the open circuit voltage diagram of the film containing a double-layer structure prepared in Examples 3-1 and 3-2 after polarization. As the porous layer of the film becomes thicker, due to the compressibility of the porous layer, the polarized film will obtain a higher open circuit voltage under the same polarization voltage. However, as the porous layer becomes thicker, the breakdown voltage of the film also decreases. Therefore, when the mass ratio of the non-solvent phase to PVTF is below 0.9, the film containing a double-layer structure can withstand relatively high voltage and have good performance output, especially when the mass ratio of the non-solvent phase to PVTF is 0.6, it has the best effect.
[0065] After testing, Examples 5-7 can also withstand relatively high voltage and have good performance output.
[0066] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived therefrom are still within the scope of protection of the present invention.
Claims
1. A method for preparing a PVTF flexible piezoelectric film having a double-layer structure, characterized in that: The steps include: The non-solvent phase, the solvent phase and the PVTF are mixed to obtain a uniform solution; wherein the non-solvent phase and the solvent are mutually soluble, and the PVTF is soluble in the solvent phase but insoluble in the non-solvent phase; The obtained uniform solution is evenly spread on a glass plate by a casting method, and then placed in a vacuum oven for evaporation at room temperature to obtain an initial film; The initial film is annealed, cooled, and polarized to obtain a piezoelectric film.
2. The method according to claim 1, characterized in that The non-solvent phase is water and ethanol; the solvent phase is tetrahydrofuran and acetone; and the PVTF is PVDF-TrFE composed of PVDF and TrFE in a molar ratio of 1-4.
3. The method according to claim 2, characterized in that The feed mass ratio of tetrahydrofuran to PVTF is 7-10, and the feed mass ratio of water to PVTF is x, where 0 <x≤0.9。 4. The method according to claim 1, characterized in that: The non-solvent phase, the solvent phase and the PVTF are mixed by stirring to obtain a uniform solution, wherein the stirring speed is 500-1000 rpm and the stirring time is 1-5 hours.
5. The method according to claim 1, characterized in that The annealing temperature is 100-150°C and the annealing time is 2-6h.
6. The method according to claim 1, characterized in that The polarization is specifically: The cooled film is cut into squares and aluminum electrodes are attached to obtain an initial device; the obtained initial device is subjected to oil bath polarization.
7. The method according to claim 6, characterized in that The oil bath polarization temperature is 60°C, the polarization voltage is 2500V-5800V, and the polarization time is 20-60min.
8. The method according to claim 1, characterized in that: After polarization, packaging is also included, specifically: Copper tapes were connected to the upper and lower surfaces of the polarized film, and the film was packaged with polyimide tape to obtain a flexible piezoelectric device.
9. A PVTF flexible piezoelectric film having a double-layer structure, characterized in that: The PVTF flexible piezoelectric film is prepared by the method for preparing a flexible piezoelectric film according to any one of claims 1 to 8, and has a double-layer composite structure of a dense layer and a porous layer.
10. Application of a PVTF flexible piezoelectric film having a double-layer structure according to claim 9 in a flexible piezoelectric sensor.
Citation Information
Patent Citations
Flexible piezoelectric thin film composite and preparing method thereof
CN110272620A
P (VDF-TrFE) composite film as well as preparation method and application thereof
CN115594874A
PVDF piezoelectric film and preparation method thereof
CN115612145A
Porous piezoelectric material with dense surface, and associated methods and devices
US20170317269A1
Cited By
PVTF flexible piezoelectric film having double-layer structure, and preparation method therefor and use thereof
WO2026129993A1